Hubungan antara Konsep Diri dan Celebrity Worship dengan Perilaku Imitasi Idol Korea pada Dewasa Awal Penyuka Drama Korea - Syifa Amalia Rosyada; Fajar Kawuryan (Lembaga Teewan Journal Solutions, 2026)
Imitation behavior among Korean popular culture fans is influenced by both internal and external factors. Self-concept serves as an internal factor that shapes how individuals evaluate observed behaviors, while celebrity worship acts as an external factor that strengthens emotional attachment to idols and encourages imitation. This study examined the relationships between self-concept, celebrity worship, and imitation behavior among emerging adults who enjoy Korean dramas using a quantitative correlational design. Data were collected through self-concept, celebrity worship, and imitation behavior scales and analyzed using multiple linear regression. The results indicated that self-concept was significantly and negatively associated with imitation behavior, whereas celebrity worship showed a significant positive association. Self-concept contributed slightly more than celebrity worship in predicting imitation behavior. Together, both variables explained 36.5% of the variance in imitation behavior. Descriptive findings revealed that most participants scored at a moderate level on all three variables, suggesting that they engaged with Korean popular culture within reasonable limits. These findings indicate that strengthening self-concept may help reduce imitation behavior among emerging adults.